Cytological spectrum of granulomatous mastitis: diagnostic and treatment challenges - Bhalla, Shalini; Agarwal, Preeti; Agarwal, Harshita; Gupta, Sameer; Mehrotra, Prateek; Raghuvanshi, Shivanjali; Sagar, Mala; Goel, Madhu Mati (International Journal of Research in Medical Sciences, 2018)
Background: Granulomatous mastitis (GM) is an inflammatory disease of the breast which clinico- radiologically mimics both inflammatory and malignant lesions. This leads to diagnostic dilemmas and delay in treatment. The aim of the present study was to review the cases diagnosed as granulomatous mastitis on Fine Needle Aspiration Cytology (FNAC) with an objective to co-relate their clinico-radiological findings, histology review where available and follow up treatment received to establish etiology and study the treatment outcome. Methods: Cytologically diagnosed cases of granulomatous mastitis were retrieved and reviewed from August 2015 - July 2017 records. Clinico-radiological co-relation, histology review where available and follow up treatment records were sought for. Results: Around 31.7% (530/1670) cases were reported as malignant, 60.3% (1009/1670) as benign proliferative and 7.9% (131/1670) as inflammatory lesions by breast FNA. 3.1% (51/1670) cases were reported as GM of all breast FNAC and 38% (51/131) of all inflammatory lesions. Follow up was available for 47 cases. Of which 26 (55.3%) cases were diagnosed as Tubercular Granulomatous mastitis (TGM) and 21(44.7%) were idiopathic granulomatous mastitis (IGM). Conclusions: Countries where tuberculosis is endemic, high degree of clinical suspicion and detailed work-up to rule out TGM is essential for all cases of granulomatous mastitis. Authors recommend a multidisciplinary workup with microbiological culture and molecular based tests on FNA material. This retrospective study illustrates that the cause of GM needs to be determined accurately for timely treatment, to avoid unnecessary delays and treatment dilemma in these patients.